The Malashan metamorphic complex in southern Tibet: Dominantly top-to-the north deformation and intrusive origin of its associated granites - Aoya, Mutsuki; Wallis, Simon R; Kawakami, Tetsuo; Lee, Jeffrey; Wang, Yu (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp.92-93